Sensors Proceedings of the Third National Conference on Sensors, February 23-25, 2016, Rome, Italy (Lecture Notes in Electrical Engineering,, 2018)
This book gathers the best papers presented at the Third Italian National Conference on Sensors, held in Rome, Italy, from 23 to 25 February 2016. The book represents an invaluable and up-to-the-minute tool, providing an essential overview of recent findings, strategies and new directions in the area of sensor research. Further, it addresses various aspects based on the development of new chemical, physical or biological sensors, assembling and characterization, signal treatment and data handling. Lastly, the book applies electrochemical, optical and other detection strategies to relevant issues in the food and clinical environmental areas, as well as industry-oriented applications.